2008
DOI: 10.1128/aac.00861-07
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Transporters CaCdr1p and CaMdr1p of Candida albicans Display Different Lipid Specificities: both Ergosterol and Sphingolipids Are Essential for Targeting of CaCdr1p to Membrane Rafts

Abstract: In this study, we compared the effects of altered membrane lipid composition on the localization of two membrane drug transporters from different superfamilies of the pathogenic yeast Candida albicans. We demonstrated that in comparison to the major facilitator superfamily multidrug transporter CaMdr1p, ATP-binding cassette transporter CaCdr1p of C. albicans is preferentially localized within detergent-resistant membrane (DRM) microdomains called 'rafts.' Both CaCdr1p and CaMdr1p were overexpressed as green fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 51 publications
2
109
0
Order By: Relevance
“…CDR1-mediated drug resistance was susceptible to changes in membrane fluidity. 17,18) Our initial investigations showed that PLE can obviously reduce the expression of CDR1, 9) which may be influenced by imbalances in membrane lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…CDR1-mediated drug resistance was susceptible to changes in membrane fluidity. 17,18) Our initial investigations showed that PLE can obviously reduce the expression of CDR1, 9) which may be influenced by imbalances in membrane lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, lipid rafts have been proposed to play important roles in polarization and compartmentalization of the plasma membrane (Wachtler & Balasubramanian, 2006), surface transport of plasma membrane ATPase (Toulmay & Schneiter, 2007), hyphal growth (Martin & Konopka, 2004), drug resistance (Hallstrom et al, 2001;Pasrija et al, 2008;Prasad et al, 2005;Thevissen et al, 2000) and localization of virulenceassociated proteins (Siafakas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have indicated important roles for lipid rafts in modulating fungal growth and pathogenesis (Hallstrom et al, 2001;Martin & Konopka, 2004;Pasrija et al, 2008;Prasad et al, 2005;Siafakas et al, 2006;Thevissen et al, 2000;Toulmay & Schneiter, 2007;Wachtler & Balasubramanian, 2006), their role in biofilm formation and associated drug resistance has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the ergosterol in the plasma membrane can be replaced by other sterol intermediates, there are some functions within the cell, such as cell division, that necessarily require some amount of ergosterol to be present (23). Furthermore, membrane integrity and composition are not only essential for the viability of the fungal cells but also influence the localization and functioning of several membrane-localized proteins (38,39). Unfortunately, with regular use, drug resistance against most antifungals has been observed FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%